Analisis Implementasi Pendidikan Inklusi pada Anak Berkebutuhan Khusus (ABK) di SDN Karawaci 5 Kota Tangerang - Nurfadillah, Septy; Hambari, Asa Amelia; Nisaa, Khairun; Maharani, Sevira Claudia (MASALIQ, 2022)
This study aims to analyze the implementation of inclusive education for children with special needs (ABK) in elementary schools. This research uses the type of qualitative research. The research subjects were elementary school teachers, assistant teachers for children with special needs, and school principals. Data collection techniques include observation, interviews, and documentation. The results showed that SDN Karawaci 5 Tangerang City implemented an inclusive program and tended to maintain the system and keep it in balance with other systems. The implementation of inclusive education is carried out by SDN Karawaci 5 Tangerang City with adjustments made to the resources it has.